Effectiveness of cognitive behavioural therapy augmentation in major depression treatment (ECAM study): study protocol for a randomised clinical trial. Issue 10 (21st October 2014) - Nakagawa, Atsuo; Sado, Mitsuhiro; Mitsuda, Dai; Fujisawa, Daisuke; Kikuchi, Toshiaki; Abe, Takayuki; Sato, Yuji; Iwashita, Satoru; Mimura, Masaru; Ono, Yutaka
Abstract : Introduction: Major depression is a serious mental disorder that causes substantial distress and impairment in individuals and places an enormous burden on society. Although antidepressant treatment is the most common therapy provided in routine practice, there is little evidence to guide second-line therapy for patients who have failed to respond to antidepressants. The aim of this paper is to describe the study protocol for a randomised controlled trial that measures the clinical effectiveness of cognitive behavioural therapy (CBT) as an augmentation strategy to treat patients with non-psychotic major depression identified as suboptimal responders to usual depression care. Methods and analysis: The current study is a 16-week assessor-blinded randomised, parallel-groups superiority trial with 12-month follow-up at an outpatient clinic as part of usual depression care. Patients aged 20–65 years with Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) Major Depressive Disorder who have experienced at least one failed trial of antidepressants as part of usual depression care, will be randomly assigned to receive CBT plus treatment as usual, or treatment as usual alone. The primary outcome is the change in clinician-rated 17-item GRID-Hamilton Depression Rating Scale (GRID-HAMD) score at 16 weeks, and secondary outcomes include severity and change in scores of subjective depression symptoms, proportion of responders and remitters, safety and quality of life. The primary population will be the intention-to-treat patients. Ethics and dissemination: All protocols and the informed consent form comply with the Ethics Guideline for Clinical Research (Japanese Ministry of Health, Labour and Welfare). Ethics review committees at the Keio University School of Medicine and the Sakuragaoka Memorial Hospital approved the study protocol. The results of the study will be disseminated at several research conferences and as published articles in peer-reviewed journals. The study will be implemented and reported in line with the CONSORT statement. Trial registration number: UMIN Clinical Trials Registry: UMIN000001218.